Kuat Tekan Beton Geopolimer Hybrid Faba Dengan Penambahan Semen PCC - Yofani, Dhea Fitra; Olivia, Monita; Wibisono, Gunawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This study investigates the effect of the alkaline/FABA ratio and the effect of extra water/FABA on FABA hybrid geopolymer concrete with aditif of portland composite cement. Treatment of geopolymer concrete is carried out at room temperature without immersion. The variations of alkali/FABA used were 0.6 and 0.65, while the variations for extra water/FABA used were 0.2 and 0.23. The results of the test show that geopolymer concrete with a variation of alkali/FABA 0.6 with a value of 18.167 Mpa, while variations of alkali/FABA 0.65 get a compressive strength of 15.568 Mpa. In the extra water/FABA 0.23 variation, the compressive strength is 15.568 Mpa, higher than the extra water/FABA 0.2 variation, which is 14.617 Mpa. Kata kunci: geopolimer, hybrid, fly ash bottom ash, portland composite cement.